Sintesis Komposit Silika Gel dari Sekam Padi – 3-Aminopropiltrietoksisilan (APTES) dengan Karbon Aktif dari Tempurung Kelapa dan Uji Adsorpsi Terhadap Logam Cd (II) - Ratih Noviasari; Yusmaniar Yusmaniar; Arif Rahman (Jurnal Riset Sains dan Kimia Terapan, 2017)
In this research, silica gel composite modified adsorbents were made with APTES and activated carbon. Silica gel comes from rice husk and activated carbon comes from coconut shell. This rice husk ash is processed in such a way as a sodium silicate solution to produce a silica gel product. The silica gel was then mixed with 3-aminopropylsylatedoxylic reagent (APTES) and activated carbon previously with ZnCl 2 solution and processed into composite. Characterization of composite synthesis using FTIR spectroscopy shows uptake of N-H, silanol (Si-OH), siloxane (Si-O-Si), and C-H bonds. The content of the silica gel composite modified by APTES and activated carbon is indicated through EDX analysis results that the composite of the synthesis has a mass percentage of each atom of 32.92% carbon, 25.88% nitrogen, 26.04% oxygen, and 15.16% silica. The results showed that the optimum pH required for the adsorption of Cd (II) ions with silica gel composite was modified with APTES and the activated carbon was 5.0 and the optimum contact time was 30 minutes. Adsorption of Cd (II) ions by silica gel composites was modified by APTES and activated carbon followed Freundlich adsorption isotherm. Therefore, adsorption occurs forming a heterogeneous monolayer layer. Keywords rice husk ash, silica gel, APTES, activated carbon, composite, adsorption